Empirical Evidence of the Effects of Public Spending on Economic Growth from BRICS - Mokoena, Nkateko (Graduate School of Business (GSB), 2021)
The topic of the impact of government spending on economic growth has previously been extensively researched, however the evidence is inconclusive to make a ruling. The purpose of this study was to examine the empirical relationship between government spending and economic growth for the BRICS (Brazil, Russia, India, China and South Africa) over the period 1994-2014 by observing GDP as the dependent variable and Education, Health, Infrastructure and Defense as the independent variables. The study was based on panel data analysis of data obtained from secondary sources. The analysis process began with summarizing the data using descriptive statistics. Following this was the process of regression analysis in order to determine the relationships between GDP and Health, Education, Defense and Infrastructure. We checked for Multicollinearity using Variance Inflation Factors (VIF's) and used the Hausman Test to determine which statistical model to use. The study followed the fixed effects statistical model. The empirical results support the null hypotheses that health, education and defense have a long-tern relationship with GDP. The study however found that there was no long-term relationship between GDP and infrastructure.